Safety and pharmacokinetics of subcutaneous administration of broadly neutralizing anti-HIV-1 monoclonal antibodies (bNAbs), given to HIV-1 exposed, uninfected neonates and infants: study protocol for a phase I trial - (:unkn) unknown (My University, 2024)
Background: The ambitious goal to eliminate new pediatric HIV infections by 2030 requires accelerated prevention strategies in high-risk settings such as South Africa. One approach could be pre-exposure prophylaxis (PrEP) with broadly neutralizing anti-HIV-1 monoclonal antibodies (bNAbs). The aim of our study is to define the optimal dose(s), the ideal combination(s) of bNAbs in terms of potency and breadth, and timing of subcutaneous (SC) administration(s) to prevent breast milk transmission of HIV.Methods: Two bNAbs, CAP256V2LS and VRC07-523LS, will be assessed in a sequential and randomized phase I, single-site, single-blind, dose-finding trial. We aim to investigate the 28-day safety and pharmacokinetics (PK) profile of incrementally higher doses of these bNAbs in breastfeeding HIV-1 exposed born without HIV neonates alongside standard of care antiretroviral (ARV) medication to prevent (infants) or treat (mothers) HIV infection. The trial design includes 3 steps and 7 arms (1, 2, 3, 4, 5, 6 and 6b) with 8 infants in each arm. The first step will evaluate the safety and PK profile of the bNAbs when given alone as a single subcutaneous (SC) administration at increasing mg/kg body weight doses within 96 h of birth: arms 1, 2 and 3 at doses of 5, 10, and 20 mg/kg of CAP256V2LS, respectively; arms 4 and 5 at doses of 20 and 30 mg/kg of VRC07-523LS, respectively. Step two will evaluate the safety and PK profile of a combination of the two bNAbs administered SC at fixed doses within 96 h of birth. Step three will evaluate the safety and PK profile of the two bNAbs administered SC in combination at fixed doses, after 3 months. Arms 1 and 6 will follow sequential recruitment, whereas randomization will occur sequentially between arms (a) 2 & 4 and (b) 3 & 5. Before each randomization, a safety pause will allow review of safety data of the preceding arms.Discussion: The results of this trial will guide further studies on bNAbs to prev
Keywords: African Research